Exploring gender preferences in farming system and tree species selection perspectives of smallholder farmers in Southern Philippines - Ureta, Joan U. (Journal of Environmental Science and Management, 2016)
Although agroforestry has been promoted in the Philippines through various programs and policies, the adoption of this practice is slower than expected. Determining the underlying reasons for the slow and declining adoption of agroforestry is vital, especially within the combined context of food insecurity, agricultural intensification and climate change. Using Analytic Hierarchy Process (AHP), this study identified the selection criteria and the priority farming systems and tree species of smallholder farmers in Lantapan, Bukidnon. Findings showed that financial benefit was the main consideration of both male and female farmers for crop selection along with other aspects of well-being (i.e regulatory services, food security). Results indicated that both groups perceived crop-based farms as more beneficial than tree-based farms. In terms of tree species, women preferred plantation crops and timber trees, while men favored fruit trees. These results showed that it is important to ensure that promotion of agroforestry will translate to tangible economic benefits for farmers.